Analisis Resepsi Kekerasan Seksual pada Perempuan dalam Film Penyalin Cahaya - Netanya Astu P.D., Raden Roro; Kusuma, Satria (School of Communication - Atma Jaya Catholic University of Indonesia, 2023)
The film “Penyalin Cahaya” is a film that addresses the issue of sexual violence against women. Sexual violence in Indonesia still occurs frequently, both verbally and non-verbally. The film